2021
DOI: 10.1002/advs.202100190
|View full text |Cite
|
Sign up to set email alerts
|

Discretizing Three‐Dimensional Oxygen Gradients to Modulate and Investigate Cellular Processes

Abstract: With the increased realization of the effect of oxygen (O 2 ) deprivation (hypoxia) on cellular processes, recent efforts have focused on the development of engineered systems to control O 2 concentrations and establish biomimetic O 2 gradients to study and manipulate cellular behavior. Nonetheless, O 2 gradients present in 3D engineered platforms result in diverse cell behavior across the O 2 gradient, making it difficult to identify and study O 2 sensitive signaling pathways. Using a layer-by-layer assembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Further, adding an external crosslinking agent enhances branching and sprouting from the ECFC clusters, thus highlighting the importance of matrix stiffness in vascular network formation [74]. A subsequent study [75] found that generating distinct Gel-HI layers allows for mechanistic studies. RNA sequencing analysis revealed the time-dependent regulation of numerous biological functions that govern the hypoxic-cluster formation, including cell survival, apoptosis, cell cycle progression, and carbohydrate metabolism.…”
Section: Engineered Hydrogels For Vascular Formationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Further, adding an external crosslinking agent enhances branching and sprouting from the ECFC clusters, thus highlighting the importance of matrix stiffness in vascular network formation [74]. A subsequent study [75] found that generating distinct Gel-HI layers allows for mechanistic studies. RNA sequencing analysis revealed the time-dependent regulation of numerous biological functions that govern the hypoxic-cluster formation, including cell survival, apoptosis, cell cycle progression, and carbohydrate metabolism.…”
Section: Engineered Hydrogels For Vascular Formationsmentioning
confidence: 96%
“…The downregulation of cyclic adenosine monophosphate signaling allowed for cell survival in a high-stress microenvironment generated by the rapid upregulation of oxidative stress and ROS (Figure 1A). Further cluster stabilization was facilitated through the upregulation of vascular cell adhesion molecule 1 (VCAM-1) and the carbohydrate metabolism in hypoxic conditions [75]. Therefore, the targeted delivery of Gel-HI with discretized oxygen gradients holds promise as the therapeutic system for eliciting angiogenic responses in ischemic diseases.…”
Section: Engineered Hydrogels For Vascular Formationsmentioning
confidence: 99%
“…Pyrogallol-mediated oxygen scavenger reaction in a microfluidic chamber led to oxygen gradient-driven directional 3D endothelial network formation in fibrinogen/hyaluronic acid hydrogels. 84 Additionally, enzymatic crosslinked hydrogel platforms presenting hypoxic gradient 85 or a distinct layered assembly of predictable O 2 tension (Figure 3B) 86 have further unveiled the molecular mechanisms mediated by HIFs-independent reactive oxygen species production for cluster-based vasculogenesis.…”
Section: Microenvironmental Perturbations Using Hydrogel Systems To F...mentioning
confidence: 97%
“…Adapted from Freeman et al 67 B , Modulation of cluster formation of endothelial colony forming cells using hypoxic hydrogel constructs. Adapted from Blatchley et al 86 C , A microfluidic hydrogel platform that maintains interstitial flow to promote in vitro human umbilical vein endothelial cell (HUVEC) microvascular networks. Millimeter length of perfusable vessels in a fibrin gel.…”
Section: Microenvironmental Perturbations Using Hydrogel Systems To F...mentioning
confidence: 99%
“…In consideration of a layer-by-layer (LBL) assembly technique as a successful measurement, it has been explored as an appealing strategy in establishing the multi-functional coating for osteogenesis ( Blatchley et al, 2021 ; Piluso et al, 2021 ). It could not only regulate local and extended drug release on the surface of PLLA acting as seal barrier but it could also orient the osteogenic differentiation of bone mesenchymal stem cells (BMSCs) and bone formation ( Lin, Hsieh, Tseng, & Hsu, 2016 ; Tsai et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%